The Potential Role of Regulatory B Cells in Idiopathic Membranous Nephropathy. (22nd December 2020) - Dong, Zhaocheng; Liu, Zhiyuan; Dai, Haoran; Liu, Wenbin; Feng, Zhendong; Zhao, Qihan; Gao, Yu; Liu, Fei; Zhang, Na; Dong, Xuan; Zhou, Xiaoshan; Du, Jieli; et al.
Abstract : Regulatory B cells (Breg) are widely regarded as immunomodulatory cells which play an immunosuppressive role. Breg inhibits pathological autoimmune response by secreting interleukin-10 (IL-10), transforming growth factor- β (TGF- β ), and adenosine and through other ways to prevent T cells and other immune cells from expanding. Recent studies have shown that different inflammatory environments induce different types of Breg cells, and these different Breg cells have different functions. For example, Br1 cells can secrete IgG4 to block autoantigens. Idiopathic membranous nephropathy (IMN) is an autoimmune disease in which the humoral immune response is dominant and the cellular immune response is impaired. However, only a handful of studies have been done on the role of Bregs in this regard. In this review, we provide a brief overview of the types and functions of Breg found in human body, as well as the abnormal pathological and immunological phenomena in IMN, and propose the hypothesis that Breg is activated in IMN patients and the proportion of Br1 can be increased. Our review aims at highlighting the correlation between Breg and IMN and proposes potential mechanisms, which can provide a new direction for the discovery of the pathogenesis of IMN, thus providing a new strategy for the prevention and early treatment of IMN.